Berserkir: a re-examination of the phenomenon in literature and life - Dale, Roderick Thomas Duncan (2014)
This thesis discusses whether berserkir really went berserk. It proposes revised paradigms for berserkir as they existed in the Viking Age and as depicted in Old Norse literature. It clarifies the Viking Age berserkr as an elite warrior whose practices have a function in warfare and ritual life rather than as an example of aberrant behaviour, and considers how usage of PDE ‘berserk’ may affect the framing of research questions about berserkir through analysis of depictions in modern popular culture. The analysis shows how berserksgangr has received greater attention than it warrants with the emphasis being on how berserkir went berserk. A critical review of Old Norse literature shows that berserkir do not go berserk, and suggests that berserksgangr was a calculated form of posturing and a ritual activity designed to bolster the courage of the berserkr.